CUSHING'S DISEASE: CONTEMPORARY APPROACHES TO DIAGNOSIS AND MANAGEMENT - Iroda Ergasheva,; E’zoza Rajabboyeva,; Aziza Abduxalilova,; Negmatova Gulzoda Shuhratovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. Cushing’s disease is a rare endocrine disorder caused by adrenocorticotropic hormone (ACTH)-secreting pituitary adenomas, resulting in endogenous hypercortisolism through chronic stimulation of the adrenal glands. Patients commonly present with characteristic clinical features, including central obesity, facial plethora, moon facies, and hirsutism. Prolonged cortisol excess is associated with substantial morbidity, affecting multiple organ systems and increasing the risk of cardiovascular and metabolic complications, respiratory disorders, psychiatric disturbances, osteoporosis, and infections. Consequently, Cushing’s disease is associated with significantly increased mortality when diagnosis and treatment are delayed. Early recognition and timely therapeutic intervention are essential to improve clinical outcomes and reduce long-term complications. This review summarizes current evidence regarding the clinical presentation, diagnostic evaluation, and management of Cushing’s disease, with emphasis on contemporary guideline-based approaches to diagnosis and treatment.